The Alkylquinolone Repertoire of Pseudomonas aeruginosa is Linked to Structural Flexibility of the FabH‐like 2‐Heptyl‐3‐hydroxy‐4(1H)‐quinolone (PQS) Biosynthesis Enzyme PqsBC. (22nd June 2018) - Witzgall, Florian; Depke, Tobias; Hoffmann, Michael; Empting, Martin; Brönstrup, Mark; Müller, Rolf; Blankenfeldt, Wulf
Abstract: Pseudomonas aeruginosa is a bacterial pathogen that causes life‐threatening infections in immunocompromised patients. It produces a large armory of saturated and mono‐unsaturated 2‐alkyl‐4(1 H )‐quinolones (AQs) and AQ N ‐oxides (AQNOs) that serve as signaling molecules to control the production of virulence factors and that are involved in membrane vesicle formation and iron chelation; furthermore, they also have, for example, antibiotic properties. It has been shown that the β‐ketoacyl‐acyl‐carrier protein synthase III (FabH)‐like heterodimeric enzyme PqsBC catalyzes the last step in the biosynthesis of the most abundant AQ congener, 2‐heptyl‐4( 1H )‐quinolone (HHQ), by condensing octanoyl‐coenzyme A (CoA) with 2‐aminobenzoylacetate (2‐ABA), but the basis for the large number of other AQs/AQNOs produced by P. aeruginosa is not known. Here, we demonstrate that PqsBC uses different medium‐chain acyl‐CoAs to produce various saturated AQs/AQNOs and that it also biosynthesizes mono‐unsaturated congeners. Further, we determined the structures of PqsBC in four different crystal forms at 1.5 to 2.7 Å resolution. Together with a previous report, the data reveal that PqsBC adopts open, intermediate, and closed conformations that alter the shape of the acyl‐binding cavity and explain the promiscuity of PqsBC. The different conformations also allow us to propose a model for structural transitions that accompany the catalytic cycle of PqsBC that might have broader implications for other FabH‐enzymes, for which such structural transitions have been postulated but have never been observed. Abstract : Dynamic and fussy : We investigate the acyl‐coenzyme A (CoA) specificity of the Pseudomonas quinolone signal biosynthesis enzyme PqsBC and find selectivity for medium‐chain acyl‐CoAs that determines the alkylquinolone repertoire of P. aeruginosa . Comparisons of several crystal structures unveil that PqsC is highly flexible, whereas PqsB is rather rigid.